Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning; Psychology of; Conditioned response; Behavior modification; Psychology; Comparative; dept.psy

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-953-404-245-599, lens.org/132-483-465-914-642 tex.type: [object Object]
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning; Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models; Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed